Analisis Keuntungan Pedagang Bunga Potong Krisan Di Kakaskasen Raya Kecamtan Tomohon Utara Kota Tomohon - Kambu, Devis Alfardo; Rengkung, Leonardus Ricky; Waney, Nordy Fritsgerald Lucky (AGRI-SOSIOEKONOMI, 2024)
The aim of this research is to analyze the business profits of cut chrysanthemum traders in Kakaskasen Raya, North Tomohon District. The research was carried out for two months from April to May 2022. Sample collection was carried out by census method and 15 respondents were obtained. This research method uses descriptive analysis by calculating profits supported by primary and secondary data. The results of the research show that the income from all businesses of cut chrysanthemum traders per week in Kakaskasen Raya, North Tomohon District in one week of the trading process is IDR 3,533,333 and the average per trader is IDR 2,021,237. The efficiency of the chrysanthemum cut flower business obtained through R/C analysis produces a value greater than one, namely 1.75. This means that the cut chrysanthemum flower business in Kakaskasen Raya, North Tomohon District is relatively profitable.